Fiat Money VS Dinar-Dirham Fungsi Uang dalam Kacamata Maqashid Syariah - Prima Dwi Priyatno (Syi`ar Iqtishadi : Journal of Islamic Economics, Finance and Banking, 2020)
Maqashid Sharia in money can be extracted from the function of that money, the most important of money function is as a media of transaction or medium of exchange, which is, the function shows the maslaha for human in overcoming problems in barter, and followed by the other functions of money with the condition of not separated from the concept of money itself in Sharia, that is by not making money as a commodity. Fiat money today has some weaknesses, among others is the value is unstable, so that perhaps one day money will be returned to dinar and dirham, or fiat money which is be back-up by gold.Maqashid Sharia in money can be extracted from the function of that money, the most important of money function is as a media of transaction or medium of exchange, which is, the function shows the maslaha for human in overcoming problems in barter, and followed by the other functions of money with the condition of not separated from the concept of money itself in Sharia, that is by not making money as a commodity. The use of dinar and dirham as money can be divided into two opinions, first it explains that money has to be based on dinar and dirham, which is it underlies the movement or campaign to back to use dinar and dirham as money, this group also allow using money that is not made from dinar or dirham, but the circulation has to be back up by gold. Another opinion is to allow using money aside from dinar and dirham, that is the use of fiat money, where using money is not limited to dinar and dirham, the use of dinar and dirham in the time of prophet Muhammad P.B.U.H. is not an excuse of necessity for Muslims in terms of Sharia, however it is in terms of culture and habit (‘urf) which is happened at that time. fiat money  today [U1] has some weaknesses, among others is the  value is unstable, so that perhaps one day money will be returned to dinar and dirham  , or fiat money which is be back-up by gold.[U2]  [U1]Perbaiki spasi!  [U2]Ukuran Font 10, spasi 1.15.  Panjang Abstrak Tidak boleh melebihi dari 150 Kata.